An Instrumentalist Account of How to Weigh Epistemic and Practical Reasons for Belief. Issue 516 (22nd November 2019) - Steglich-Petersen, Asbjørn; Skipper, Mattias
Abstract: When one has both epistemic and practical reasons for or against some belief, how do these reasons combine into an all-things-considered reason for or against that belief? The question might seem to presuppose the existence of practical reasons for belief. But we can rid the question of this presupposition. Once we do, a highly general 'Combinatorial Problem' emerges. The problem has been thought to be intractable due to certain differences in the combinatorial properties of epistemic and practical reasons. Here we bring good news: if we accept an independently motivated version of epistemic instrumentalism—the view that epistemic reasons are a species of instrumental reasons—we can reduce The Combinatorial Problem to the relatively benign problem of how to weigh different instrumental reasons against each other. As an added benefit, the instrumentalist account can explain the apparent intractability of The Combinatorial Problem in terms of a common tendency to think and talk about epistemic reasons in an elliptical manner.